PENDAMPINGAN TASYAKUR KEMERDEKAAN REPUBLIK INDONESIA DI KAMPUNG KRASAK KECAMATAN MOJOTENGAH KABUPATEN WONOSOBO - Ahmad Fatih; Robingun Suyud El Syam (Fakultas Teknik Universitas Cenderawasih, 2022)
Independence is a very coveted dream for every country, Indonesia is one of those who received this gift, so every citizen has the right to celebrate it as a form of gratitude. Through the strategy of committee meetings, social services, village parades, ceremonies commemorating the independence of the Republic of Indonesia, competitions, reflection & entertainment activities, and village celebrations, concluded: Activities in the context of celebrating the independence day of the Krasak residents succeeded in increasing the enthusiasm of the residents. Activities produce reflections on meaning: (1), independence is not the end of struggle, (2) freedom from colonialism, (3) as a unifying moment for the nation, (4) instilling values ​​of tolerance and mutual respect, and (5) being a signal for the awakening of the nation. .